Cranial meningiomas in 411 neurofibromatosis type 2 (NF2) patients with proven gene mutations: clear positional effect of mutations, but absence of female severity effect on age at onset. Issue 4 (28th January 2011) - Smith, Miriam J; Higgs, Jenny E; Bowers, Naomi L; Halliday, Dorothy; Paterson, Joan; Gillespie, James; Huson, Susan M; Freeman, Simon R; Lloyd, Simon; Rutherford, Scott A; King, Andrew T; Wallace, Andrew J; et al.
Abstract : Background: Meningiomas have been reported to occur in approximately 50% of neurofibromatosis type 2 (NF2) patients. The NF2 gene is commonly biallelically inactivated in both schwannomas and meningiomas. The spectrum of NF2 mutations consists mainly of truncating (nonsense and frameshift) mutations. A smaller number of patients have missense mutations, which are associated with a milder disease phenotype. Methods: This study analysed the cumulative incidence and gender effects as well as the genotype–phenotype correlation between the position of the NF2 mutation and the occurrence of cranial meningiomas in a cohort of 411 NF2 patients with proven NF2 mutations. Results and conclusion: Patients with mutations in exon 14 or 15 were least likely to develop meningiomas. Cumulative risk of cranial meningioma to age 50 years was 70% for exons 1–3, 81% for exons 4–6, 49% for exons 7–9, 56% for exons 10–13, and 28% for exons 14–15. In the cohort of 411 patients, no overall gender bias was found for occurrence of meningioma in NF2 disease. Cumulative incidence of meningioma was close to 80% by 70 years of age for both males and females, but incidence by age 20 years was slightly increased in males (male 25%, female 18%; p=0.023). Conversely, an increased risk of meningiomas in women with mosaic NF2 disease was also found.